Sister Boniface mysteries. Season 2 [videorecording (DVD)] - Tindall, Jude (BBC, 2023)
It's the '60s and Sister Boniface, with her aptitude for detective work, is an invaluable asset to the Great Slaughter Police Department. Her faith in forensics is only rivaled by her passion for investigation. If there's evidence to be found, Boniface will find it. In this series, the sister forces a murderer into checkmate at a chess tournament, takes a spin at a pirate radio station, confronts a coven of witches, and defends her reputation as the conviction of her greatest adversary, 'The Good Samaritan,' comes into question.